2023
DOI: 10.1123/jege.2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Toxicity Toward Women in Game-Based Communities

Matthew Belskie,
Hanlin Zhang,
Bradley M. Hemminger

Abstract: Prior research into gaming toxicity in game-specific Reddit communities nearly always considers toxicity in aggregate, and so provides very few clues for a valid coding scheme for isolating toxic language and triggers that specifically target women gamers. Existing research offers a starting place for devising valid methods for measuring and detecting toxic language and toxic triggers within specified data sets, but that research is less useful is its applicability to game-related forms of toxicity targeting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…In our sample, 40% of esports athletes on a team or club were women. Researchers have suggested that females might be hesitant to participate in esports because gaming is typically viewed as a male-dominated activity, the industry has marginalized females, and gaming culture has a history of sexism against females (Belskie et al, 2023;Cote et al, 2023). Considering the barriers, females may be even more inclined to include vigorous physical exercise in their esports training routine in an effort to prove themselves in what many perceive as a maledominated activity.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, 40% of esports athletes on a team or club were women. Researchers have suggested that females might be hesitant to participate in esports because gaming is typically viewed as a male-dominated activity, the industry has marginalized females, and gaming culture has a history of sexism against females (Belskie et al, 2023;Cote et al, 2023). Considering the barriers, females may be even more inclined to include vigorous physical exercise in their esports training routine in an effort to prove themselves in what many perceive as a maledominated activity.…”
Section: Discussionmentioning
confidence: 99%
“…Gaming is structured as an "adolescent, white, male activity" in which "the experiences of women and people of color are often overlooked" (Gray, 2014, p. 75). In online spaces, abuse and harassment of nonmale, non-White gamers is frequent enough to be quantitatively measured (Belskie et al, 2023;Evans & Llano, 2023). The persistent stranglehold on video gaming exercised by this toxic geek masculinity (Salter & Blodgett, 2017) is due, in part, to a lack of player visibility.…”
mentioning
confidence: 99%